SELF-EFFICACY FROM A PHILOSOPHY OF SCIENCE PERSPECTIVE IN EMPOWERING POSTPARTUM MOTHERS IN MIDWIFERY PRACTICE - Risnawati Risnawati; Suryo Ediyono (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The postpartum period is a crucial period with physiological, psychological, and social changes that can impact the health of both mother and baby. A mother's inability to adapt risks postpartum depression, poor breastfeeding success, and suboptimal infant care. Therefore, maternal empowerment is a crucial strategy, one of which is influenced by self-efficacy (confidence in one's own abilities). This study aimed to analyze the relationship between self-efficacy and postpartum maternal empowerment using a quantitative cross-sectional design among 40 postpartum mothers at the Sulaa Community Health Center in Baubau City (2025). Data were collected through questionnaires and analyzed using the Chi-Square test. The results showed that the majority of respondents had high self-efficacy (60%) and good empowerment (65%), with a significant relationship between the two (p = 0.003). Mothers with high self-efficacy tended to be more empowered. In conclusion, self-efficacy plays a crucial role in postpartum maternal empowerment and needs to be enhanced through education, counseling, and support from healthcare professionals.